A tetrahedral coordination of Zinc during transmembrane transport by P-type Zn2+-ATPases - Raimunda, Daniel Cesar (2012)
Zn2 + is an essential transition metal required in trace amounts by all living organisms. However, metal excess is cytotoxic and leads to cell damage. Cells rely on transmembrane transporters, with the assistance of other proteins, to establish and maintain Zn2 + homeostasis. Metal coordination during transport is key to specific transport and unidirectional translocation without the backward release of free metal. The coordination details of Zn2 + at the transmembrane metal binding site responsible for transport have now been established. Escherichia coli ZntA is a well-characterized Zn2 +-ATPase responsible for intracellular Zn2 + efflux. A truncated form of the protein lacking regulatory metal sites and retaining the transport site was constructed. Metrical parameters of the metal-ligand coordination geometry for the zinc bound isolated form were characterized using x-ray absorption spectroscopy (XAS). Our data support a nearest neighbor ligand environment of (O/N)2S2 that is compatible with the proposed invariant metal coordinating residues present in the transmembrane region. This ligand identification and the calculated bond lengths support a tetrahedral coordination geometry for Zn2 + bound to the TM-MBS of P-type ATPase transporters.